Learning, teaching, and social media : a generational approach - McWhirter, Andrew (Abingdon, Oxon ; New York, NY: Routledge, 2024)
"Employing a unique generational approach, this book critically assesses social media in educational contexts across all educational levels: from primary and secondary schools to further and higher education, proposing a schema for social media literacy (SML). Using research obtained from fieldwork observations conducted in online teaching groups, surveys, and in-depth interviews with teachers and educators on the topic of social media and education, chapters interrogate the historical relationship between educator and learner, and use the frame of expert methodology to understand what educators themselves consider important about social media and education relative to their sectors. Bringing together current literature from education, learning and media technologies, along with longstanding debates around technological influence, chapters also draw on audience and communication studies, psychology and arts and humanities at a time when many different disciplines are trying to understand what social media means to our society. This interdisciplinary volume will be of great interest to academics, researchers and postgraduates in the fields of technology in education, media literacy, and critical digital media. Practitioners involved in the sociology of education will also find the book of use"--
Keywords: Social media in education; Media literacy -- Study and teaching; Internet in education; Education -- Effect of technological innovations on; EDUCATION / Computers & Technology; EDUCATION / General; SOCIAL SCIENCE / Media Studies